Biofuels and developing economies: Is the timing right? - Msangi, Siwa; Evans, Martin (Wiley, 2013)
In this article, we discuss some key aspects of biofuel production in developing countries, and where constraints and tradeoffs are likely to occur. We use the example of two countries, Senegal and India, to highlight some of the issues of cost competitiveness, problems with ensuring stable supply of feedstock as well as critical missing links in the biofuels value chain that pose problems to scaling up national programs in these countries. We discuss the particularly problematic nature of jatropha, as a biodiesel feedstock, and underline some helpful guiding principles that can help country‐level policy. We point to an underlying “duality” between a well‐functioning food system and favorable conditions for agribusiness enterprises, such as biofuels, and the relevance it has to achieving food security goals.